Blaze me a sun : a novel about a crime - Carlsson, Christoffer, 1986- (Hogarth, 2023)
"In February 1986, the Halland police receive a call from a man who claims to have raped a woman. I'm going to do it again, he says. Then the call cuts off. By the time policeman Sven Jörgensson reaches the victim, she's taking her last breath. For Sven and his son Vidar, this will prove a decisive moment. On the same night, Sweden plunges into a state of shock after the murder of the prime minister. Could there possibly be a connection? Two more women fall victim to the local serial killer without Sven being able to stop him. Over time Sven becomes obsessed with the case, while Vidar, longing to be closer to his father, joins the police. For years Sven remains haunted by the murders he cannot solve and paralyzed by fear that the killer might strike again. Eventually Sven retires in defeat from the police. Having failed to catch the murderer, he passes his obsession to his son. Many years later, the case unexpectedly resurfaces when a novelist returns home to Halland after a failed marriage and sputtering career. The writer befriends a retired police officer, a former colleague of Sven's, who helps the novelist--our narrator--unspool the many strands of this engrossing tale about a community confronting its collective guilt"--